Selection of quality improvement initiatives: an initial conceptual model - Musli Mohammad; Robin Mann; Nigel Grigg; Jürgen P. Wagner (Penerbit ukm, 2009)

(untitled)
There are numerous quality improvement initiatives that can be used by organisations to improve quality, productivity and sustainability towards achieving excellence, such as Six Sigma, Lean, Business Process Reengineering, ISO9000, and Benchmarking. Nevertheless, in reality, no single initiative can solve all problems effectively in the organisation. The right initiatives to be used may vary depending on several contextual factors, for instance, the current maturity level of the organisation, areas in which the initiatives are implemented, organisation type and size, and the capabilities of the workforce. Moreover, there is a lack of clear understanding by people regarding when, where and how to implement initiatives. Due to this situation, many organisations face difficulties in selecting suitable improvement initiatives according to the context. This paper discusses issues of selecting initiatives and proposes an initial conceptual model to select suitable quality improvement initiatives on the journey towards achieving organisational / business excellence (BE). The proposed initial conceptual model focuses on the critical factors that should be considered in selecting suitable quality improvement initiatives as well as some examples of the main initiatives to implement to improve performance according to the level of BE maturity and areas of implementation